PANCASILA AS A LEGAL SCIENCE PARADIGM - Dini Amalia Fitri (International Journal of Law Reconstruction, 2019)
The Pancasila legal paradigm is a legal category that is unique to Indonesia, but is universally objective. This jurisprudence is based on God Almighty. This jurisprudence is loaded with the values of Almighty God and other values in the frame of the value of Almighty God. The existence and existence of this legal knowledge for the people of Indonesia is a gift. To change the paradigm of higher education in the field of law, it must start by changing education fundamentally as a dynamic subject of the reality of people's lives so that understanding of law becomes holistic, visionary, and meaningful. One way to elevate Pancasila as the nation's identity and be known by the nations of the world, is by practicing the values contained in the five principles, by synergizing Pancasila values with the legal education curriculum in Indonesia, so that it will produce law graduates who live the values of Pancasila.